İstanbul'da eski eser tahribi 1908-1938 - Sıçrayık, Anılcan (My University, 2019)
İstanbul’da 1908-1938 yılları arasında yaşanan eski eser tahripleri bu tezin ana konusunu teşkil etmektedir. 19. Yüzyılın ikinci yarısında şehircilik çalışmaları ile tanışan İstanbul, modern bir kent görünümü almaya başlarken pek çok tarihi eserini de kaybetmiştir. 20. yüzyılın ilk on beş yılında yaşanan eski eser tahripleri öyle bir boyuta gelmiştir ki, devlet hukuki olarak tedbir almak zorunda kalmıştır. Cumhuriyet dönemine gelindiğinde ise ekonomik sıkıntılar ve yapılan inkılâp hareketleri ile toplum nezdindedeki eski eser algısının belirleyici nitelikte olduğu görülmektedir. Bu kapsamda tezin ana omurgasını oluşturan bölümde Osmanlı’dan Cumhuriyet’e intikal eden eski eserlerin hukuki durumu ve eski eserlere sahip idarelerin ekonomik koşulları hakkında bilgi verildikten sonra tahriplerin sebepleri örnekler üzerinden tespit edilmeye çalışılmıştır. Bu çerçevede tahrip sebebi olarak gösterilebilecek yedi ayrı başlık ortaya çıkmıştır; doğa olaylarının yarattığı tahribat, hırsızlık dolayısıyla yaşanan tahribat, eski eser bilinci eksikliğinden kaynaklanan tahribat, ihmal ve bakımsızlık dolayısıyla yaşanan tahribat, vakıf müessesesinin çözülmesi dolayısıyla yaşanan tahribat, siyasi ve ideolojik sebeplerden kaynaklanan tahribat ve imar faaliyetleri dolayısıyla yaşanan tahribat.

ABSTRACTIstanbul is one of the leading historical cities in the world with both its number and quality of historical places. Istanbul, the sucessor to the great civilizations, left to agains Ankara in 1923 as the capital city. From that date until today, Istanbul has lost the distinction of being the largest city in Turkey in terms of population. By the early 20th century, the city's increasingly crowded population reached big problems. Dusty roads, industrial areas very close to residential areas, districts not yet completed water and sewerage infrastructure, fire places, and neighborhoods surrounded by dead-end streets are some of these problems. While these problems were sought in modern ways many historical monuments built in different periods in terms of architecture and art were destroyed, from the second constitutional monarchy period (1908)In the thesis study, destruction of antiquities in Istanbul between the years 1908-1938 was studied. After giving information about the general situation of the ancient monuments from Ottoman Empire to the Republic, the reasons of the destruction were tried to be determined by examples. In this context, 7 separate titles have emerged as the reason for destruction; Destruction of natural events. Damage caused by theft. Destruction caused by the lack of ancient monument consciousness. Destruction resulting from negligence and neglect. Destruction resulting from the problems of the Foundations. Destruction due to political and ideological reasons. Destruction due to reconstruction activities.
Keywords: Ancient Monuments; Antiquities; Destructions; Eski eserler; Foundations; Istanbul (Turkey); İmar; İstanbul; İstanbul (Türkiye); Reconstruction; Vakıflar Istanbul; Yıkımlar